2022
DOI: 10.1002/ps.6882
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetically engineered soybean and Amaranthus weeds on biological and reproductive parameters of Spodoptera cosmioides (Lepidoptera: Noctuidae)

Abstract: BACKGROUND: In soybean fields containing insecticide-and herbicide-resistant genetically engineered varieties, some weed species have increasingly become difficult to manage and may favor the population growth of secondary pests like Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae). To test this hypothesis, we measured life-history traits, population growth parameters and adult nutrient content of S. cosmioides reared on foliage from four Amaranthus species, from Cry1Ac Bt and non-Bt soybean varieties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The interference of the biotic factor may be related to insects feeding on plants with low nutritional quality, which can affect their biological, physiological, and behavioral characteristics, through the reduction of size, weight, survival, the intensity of consumption by larvae, longevity, and potential reproductive, etc. (Cabezas et al 2013;Gomes et al 2017;Schowalter 2016b;Silva et al 2017;Silva et al 2019;Zamora Belli et al 2020;Páez Jerez et al 2022;Parra et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The interference of the biotic factor may be related to insects feeding on plants with low nutritional quality, which can affect their biological, physiological, and behavioral characteristics, through the reduction of size, weight, survival, the intensity of consumption by larvae, longevity, and potential reproductive, etc. (Cabezas et al 2013;Gomes et al 2017;Schowalter 2016b;Silva et al 2017;Silva et al 2019;Zamora Belli et al 2020;Páez Jerez et al 2022;Parra et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the transgenic traits were also described in another case in Brazil [103]: according to their findings, the spread of Amaranthus weeds (Amaranthus palmeri) in soybean fields is facilitated by the cultivation of the transgenic herbicide-resistant plants. It was found that if black armyworm larvae (Spodoptera cosmioides) fed on A. palmeri, this had positive effects on its biological and reproductive parameters.…”
Section: Some Experience From Transgenic Plantsmentioning
confidence: 96%